Ribosome-binding Sequences (RBS) Engineering of Key Genes in Escherichia coli for High Production of Fatty Alcohols - Chen, Ruonan; Liu, Yilan; Zhong, Wei; Hao, Xuemi; Mu, Tingzhen; Yang, Maohua; Xing, Jianmin (Biotechnology and bioprocess engineering, 2022)
Fatty alcohols are widely used in the fields of food, pharmaceutical and renewable energy and so on, thus biosynthesis of fatty alcohols has attracted wide attention in recent years. However, the concentration of fatty alcohols is still at a low level. In this paper, we constructed an Escherichia coli strain with high yield of fatty alcohols through the combinatorial regulation of three key genes of fabH , fabZ , and far . Firstly, we designed new ribosome-binding sequences (RBS) of fabH and fabZ with 10-fold strengths compared to the original ones by RBS calculator, separately. Secondly, we engineered the starting strain MGL1 by replacing the original RBS with designed ones, which resulted in MGLHS ( fabH -RBS1), MGLZS ( fabZ -RBS2), and MGLHZS ( fabH -RBS1/ fabZ -RBS2), respectively. Thirdly, the plasmid pL1 harboring far gene was transferred into above strains to test fatty alcohols production under the induction of different isopropyl-β-D-thiogalactoside concentrations. The results showed that the concentration of fatty alcohols in strains MGLHS- far , MGLZS- far and MGLHZS- far reached 2.75 g/L, 2.54 g/L and 3.82 g/L, respectively, which increased 35%, 25% and 88% than that of the starting strain MGL1- far . The fatty alcohols reached 9.35 g/L in fed batch fermentation with MGLHZS- far , of which the main components were two saturated fatty alcohols (C14:0 and C16:0) and two unsaturated fatty alcohols (C16:1 and C18:1). The results demonstrated that combinatorial regulation of three key genes of fabH , fabZ , and far in E. coli can achieve high-yield production of fatty alcohols.